The Potential of Generative Artificial Intelligence Based on Applications in Judicial Supervision in An Efforts to Reduce Corruption, Collusion, and Nepotism - Adeng Septi Irawan (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2025)
Time has become more advanced and artificial intelligence technology AI (Artificial Intelligence) is developing rapidly. Electronic court-based court technology (e-Court) is starting to become commonplace in the Supreme Court Jurisdiction. However, in practice, the behavior of corruption, collusion, and nepotism still occurs recently in the Supreme CourtJurisdiction, ranging from cases of bribery of judges in handling cases, arrogant behavior of judges in trials, to the behavior of judges or employees committingethical and legal violations. It seems like an endless stream of incidents that should not exist, due to technological advances, are instead emerging. This research aims to provide new ideas regarding the potential of Generative. Application-based AI (Artificial Intelligence) in the context of Judicial Supervision to reduce corruption, collusion, and nepotism behavior. This study applies a library research approach study (Literature Study) with an analytical prescriptive method (analytical method using legal materials and information and communication technology materials to produce appropriate recommendations in application-based decision making) and application-based legal hermeneutics (interpretation). The results of this research data indicate that there is a fairly large anomaly, where advances in information and communication technology have not been able to suppress the behavior of corruption, collusion, and nepotism in the judiciary. This problem emerged the idea of ​​using application-based Generative AI (Artificial Intelligence) in judicial supervision management. Generative AI (Artificial Intelligence) is a type of AI that can create new content and ideas.